Analysis of Factors Associated with the Management of Code Blue In Patients With Emergency At Ulin Hospital - ica lisnawati; Wahyudin; Solikin (UrbanGreen, 2019)
Code blue is one of the emergency procedure codes that must be activated immediately if someone is found in a condition of cardiac respiratory arrest in the hospital area. code blue response team or code blue team is a team formed by the hospital in charge of responding to the condition of the code blue in the hospital area. This study aims to determine the correlation of HR, Facilities, Response time, and SPO factors with code blue management in the hospital. This research is a quantitative research with descriptive analysis method with factor design test, a sample of 33 code blue teams. The results showed that there was a correlation and influence of factors (sub-variables) of human resources, facilities, response time and standard operating procedures with code blue governance in hospitals. The strength of the factors in the management of code blue in hospitals in a sequence is the facility then continued with the response time factor, human resources and finally the standard operational procedure factors for the code blue team's management in emergency patients.